2021
DOI: 10.3390/brainsci11040473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Interventions with Aerobic Physical Exercise and Cognitive Training on Cognitive Function in Stroke Patients: A Systematic Review

Abstract: (1) Background: Stroke is a major cause of permanent disability in multiple functions, including the cognitive domain. Since both cognitive training and aerobic physical exercise may exert positive effects on cognition after stroke, one may expect synergistic benefits when combining both interventions. (2) Methods: We carried out a systematic search of studies testing, in adult stroke patients, whether structured aerobic exercise combined with cognitive training led to higher cognitive benefits than either of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…Ultimately, according to the results obtained from the present research and previous studies, exercise and physical activities appear to prevent or postpone disability and lead to the patientsʹ recovery by way of two mechanisms: (i) cognitive mechanisms, including the many positive effects of physical activity on the spirit and mind and vitality and also the direct effects of exercise on physical fitness factors, releasing the mind of its treatment mode and inducing a sense of liveliness [3,51], and (ii) physiological mechanisms, includ-ing increased blood circulation, blood pressure control, increased oxygen tolerance, improved neurogenesis and angiogenesis, mitochondrial viability, inhibition of the acute inflammatory response, neuronal apoptosis and protection of the blood-brain barrier [14,32,52].…”
Section: Discussionmentioning
confidence: 61%
“…Ultimately, according to the results obtained from the present research and previous studies, exercise and physical activities appear to prevent or postpone disability and lead to the patientsʹ recovery by way of two mechanisms: (i) cognitive mechanisms, including the many positive effects of physical activity on the spirit and mind and vitality and also the direct effects of exercise on physical fitness factors, releasing the mind of its treatment mode and inducing a sense of liveliness [3,51], and (ii) physiological mechanisms, includ-ing increased blood circulation, blood pressure control, increased oxygen tolerance, improved neurogenesis and angiogenesis, mitochondrial viability, inhibition of the acute inflammatory response, neuronal apoptosis and protection of the blood-brain barrier [14,32,52].…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, among the benefits related to physical conditioning, such as functionality, mood, and cardiovascular health, it was identified that aerobic exercise might potentiate the neuroplasticity process with more robust responses in training programs with moderate to high-intensity exercises ( Penna et al, 2021 ). Finally, cognitive improvement is indicated in aerobic exercises combined with cognitive training, especially computerized training ( Amorós-Aguilar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis by Sun et al (2021) showed significant benefits of combined cognitive exercise interventions (more specifically, cognitive behavioral training, computer-assisted cognitive training and physical training) compared to no intervention, delayed intervention, sham intervention, or passive training in patients with cognitive impairment post-stroke in executive, attention, and memory functions. In addition, another review that investigated the effects of aerobic exercise combined with cognitive training (mostly computerized) found that the combined intervention was associated with post-intervention improvement on at least one cognitive test across all included studies ( Amorós-Aguilar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, although promising, results remain inconclusive due to study heterogeneity and methodological limitations. Some authors have further analyzed the additive gains of combining CCT with PE in stroke patients, with preliminary positive results ( Amorós-Aguilar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%